PENGARUH PENERAPAN REWARD TERHADAP MOTIVASI BELAJAR MATEMATIKA SISWA KELAS V DI MI BUSTANUL IMAN PENGANDON, KARANGDADAP PEKALONGAN - Hana Putri; Fika Ramadhani; Muhammad Nashrulloh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the direct effect of reward provision on fifth-grade students' mathematics learning motivation at MI Bustanul Iman Pengandon using a quantitative approach with a quasi-experimental pretest–posttest method. All 13 fifth-grade students were sampled through a saturated sampling technique. Theresearch instrument, a learning motivation questionnaire, was administered before and after treatment. Data analysis began with a normality test as a prerequisite, then continued with a paired sample t-test using SPSS. The average learning motivation score increased from 78.31 before treatment to 86.69 after reward provision. The results of the normality test showed a normal data distribution, and the t-test produced a significance value of 0.000 <0.05, so the alternative hypothesis was accepted. These findings confirm that reward provision has a positive and significant effect on fifth-grade students' mathematics learning motivation at MI Bustanul Iman Pengandon. The results of this study are expected to be a reference for teachers in designing learning strategies that can increase learning motivation, as well as provide a basis for consideration for the application of rewards in the context of basic education.